WAVY GROWTH Arabidopsis E3 ubiquitin ligases affect apical PIN sorting decisions - Konstantinova, Nataliia; Hoermayer, Lukas; Glanc, Matouš; Keshkeih, Rabab; Tan, Shutang; Di Donato, Martin; Retzer, Katarzyna; Moulinier-Anzola, Jeanette; Schwihla, Max; Korbei, Barbara; Geisler, Markus; Friml, Jiří; et al. (Nature communications, 2022)
Directionality in the intercellular transport of the plant hormone auxin is determined by polar plasma membrane localization of PIN-FORMED (PIN) auxin transport proteins. However, apart from PIN phosphorylation at conserved motifs, no further determinants explicitly controlling polar PIN sorting decisions have been identified. Here we present Arabidopsis WAVY GROWTH 3 (WAV3) and closely related RING-finger E3 ubiquitin ligases, whose loss-of-function mutants show a striking apical-to-basal polarity switch in PIN2 localization in root meristem cells. WAV3 E3 ligases function as essential determinants for PIN polarity, acting independently from PINOID/WAG-dependent PIN phosphorylation. They antagonize ectopic deposition of de novo synthesized PIN proteins already immediately following completion of cell division, presumably via preventing PIN sorting into basal, ARF GEF-mediated trafficking. Our findings reveal an involvement of E3 ligases in the selective targeting of apically localized PINs in higher plants.
Keywords: proteiny huseníčku; kořeny rostlin; Plant Roots; Protein Transport; Arabidopsis Proteins; kyseliny indoloctové; Ubiquitin-Protein Ligases; ubikvitinligasy; Indoleacetic Acids; transport proteinů; Arabidopsis